Knowledge, awareness and behaviour among Malaysians towards the impact of climate change: case study in Klang valley / Syed Zainal Abidin Jamallulail Syed Abd. Aziz … [et al.] - Syed Abd. Aziz, Syed Zainal Abidin Jamallulail; Mohamad, Nur Dalila; Mohd Zaki, Zuhaida; Maskin, Mazleha; Amir, Amnorzahira (2022)
Public knowledge, awareness and behaviour on climate change are crucial to prevent climate change. This study investigates the level of knowledge, awareness and behaviour of Malaysian society on the impact of climate change (Case study in Klang Valley). Adopting a descriptive survey research design, a self-designed questionnaire entitled "Climate Change Awareness” was conducted on a sample of 467 respondents from three (3) main groups (university students, public and government servants). Cronbach's alpha (α) for this study is 0.749, indicating an acceptable level of internal reliability of the scale with this specific sample. The finding indicates that most of the respondents have an average level of knowledge (41.22%) from different levels of education. The level of awareness and behaviour among the respondents was also very weak and fragile. Approximately 55.3% of respondents are not aware of the impact of climate change on the environment, economy and human health. Although the government has promoted its initiatives and policy regarding climate change, it cannot be presumed that the society is having a high level of knowledge awareness and behaviour about climate change. In addition, this study also measured the effectiveness of the national policy on climate change in Malaysian society. This study offers the decision makers some fundamental insights regarding public knowledge, awareness and behaviour towards climate change that could potentially assist in promoting responsive policies and strategies to reduce the impact of climate change.